Pelatihan dan Pendampingan Penggunaan Teknologi Tepat Guna Untuk Meningkatkan Produksi Minyak Kemiri - Abdianto Nggego, Dedy; Marsujitullah, Marsujitullah; Ama Longgy, Dodhy Hyronimus (Abdimas Mandalika, 2025)
Abstract:  Local economic empowerment promotes community self-sufficiency and regional growth. The development of Micro, Small, and Medium Enterprises (MSMEs) through the Less Contact Economy concept is expected to enhance community welfare by optimizing technology for more efficient and competitive production and marketing processes. This program aims to improve the welfare of the Kanum Tribe in Yanggandur Village by strengthening the agricultural-based MSME sector. The Community-Based Participatory Research (CBPR) approach is implemented through five key stages: socialization, training, technology implementation, mentoring and evaluation, and program sustainability enhancement. The training focuses on production, management, and marketing, covering the use of a seed oil press machine, digital financial record-keeping through the “Buku Kas” application, and digital marketing strategies. The results indicate that utilizing the oil press machine increased candlenut oil productivity threefold and reduced the extraction process duration from seven days to two days. This program emphasizes technical assistance, continuous evaluation, and strategic partnerships with stakeholders to expand market reach and strengthen product distribution.Abstrak: Pemberdayaan ekonomi lokal mendorong kemandirian masyarakat dan pertumbuhan daerah. Pengembangan UMKM melalui konsep Less Contact Economy diharapkan meningkatkan kesejahteraan dengan mengoptimalkan teknologi untuk produksi dan pemasaran yang lebih efisien dan kompetitif. Program ini bertujuan untuk meningkatkan kesejahteraan masyarakat Suku Kanum di Kampung Yanggandur melalui penguatan sektor UMKM berbasis pertanian. Pendekatan Community Based Participatory Research (CBPR) diterapkan dengan lima tahapan utama, yaitu sosialisasi, pelatihan, implementasi teknologi, pendampingan dan evaluasi, serta penguatan keberlanjutan program. Pelatihan difokuskan pada aspek produksi, manajemen, dan pemasaran, mencakup penggunaan mesin press minyak biji-bijian, penerapan pencatatan keuangan digital melalui aplikasi “Buku Kas”, serta strategi pemasaran berbasis digital. Hasil kegiatan menunjukkan bahwa penggunaan mesin press minyak mampu meningkatkan produktivitas minyak kemiri hingga tiga kali lipat, serta mempercepat proses ekstraksi dari 7 hari menjadi 2 hari. Program ini menitikberatkan pada pendampingan teknis, evaluasi berkelanjutan, serta kemitraan strategis dengan pemangku kepentingan guna memperluas jangkauan pemasaran dan memperkuat distribusi produk.